Circular discontinuities detection in welded joints using Circular Hough Transform - Hafizal, Yazid; Haniza, Yazid; Mohd Harun; Shukri Mohd; A. Aziz, Mohamed; Mohamed Rizon, Mohamed Juhari; Shaharudin, Sayutia (Elsevier B.V., 2009)
Link to publisher's homepage at www.elsevier.com